تقدير الإنتاج الرسوبي للأحواض المائية غير المرصودة باستخدام تقنية النماذج التكاملية - محمد رشيد, أنس محمود; عبو حسن, عبد الغني (Latakia University Journal -Engineering Sciences Series, 2019)
The aim of this research is to estimate the sediment yield of ungauged basins by using the integrating model technique. A Geographical Information System (GIS), coupled with the Universal Soil Loss Equation (USLE) model by applying spatial program with advanced language programming (Visual Basic 6), is used to facilitate database development, manipulation, and output display. The 403 km2 watershed is divided into 200 x 200 m grid cells, and gross soil erosion for each cell is first predicted by the USLE model. The Arc/Info GIS utilities are used to calculate the total mass of sediment moving from each cell to the nearest stream network. In addition, a watershed of (36) effective rainstorms is simulated; the sediment yield ranges between (16 and1908 tons) for rainfall ranging between (15.5 and 79.9) mm; the results have demonstrated that the eroded sediment yield is closely related to rainfall يتناول البحث الحالي تقدير الإنتاج الرسوبي للوديان غير المرصودة وذلك باستخدام تقنيات النماذج الرقمية الحاسوبية المتكاملة، حيث تم في البحث الحالي الربط بين نظام المعلومات الجغرافية (GIS) مع نموذج حاسوبي تم بناؤه لتقدير الإنتاج الرسوبي من خلال برنامج أُعد لهذا الغرض وباستخدام لغة برمجية (Visual Basic 6) وباستخدام معادلة فقدان التربة (USLE). تم استخدام حوض مائي غير مرصود كنموذج للدراسة بمساحة (403 km2) حيث تم تقسيمه إلى شبكة من الخلايا بأبعاد (200 x 200 m) تعتمد في حساب الإنتاج الرسوبي لها وباستخدام معادلة فقدان التربة (USLE) ثم يتم حساب صافي الرسابات المنقول من خلال شبكة البزل في حوض الدراسة مع كمية الإنتاج الرسوبي عند منفذ الحوض باستخدام نظام (Arc/Info GIS). وقد تم في البحث الحالي محاكاة الإنتاج الرسوبي لـ (36) عاصفة مطرية مؤثرة وتراوحت كمية الإنتاج الرسوبي بين (16-1908) tons لهطول مطري يتراوح بين (15.5 – 79.9 mm)، وبينت النتائج بشكل واضح بان الإنتاج الرسوبي مرتبط مع الهطول المطري بعلاقة تم استنتاجها للحوض المدروس.